ESCRT-III-Associated Protein ALIX Mediates High-Affinity Phosphate Transporter Trafficking to Maintain Phosphate Homeostasis in Arabidopsis. Issue 9 (4th September 2015) - Cardona-López, Ximena; Cuyas, Laura; Marín, Elena; Rajulu, Charukesi; Irigoyen, María Luisa; Gil, Erica; Puga, María Isabel; Bligny, Richard; Nussaume, Laurent; Geldner, Niko; Paz-Ares, Javier; Rubio, Vicente
Abstract : ALIX associates with the ESCRT-III complex to mediate trafficking to the vacuole of protein cargoes, including phosphate transporters and brassinosteroid receptor BRI1. Abstract: Prior to the release of their cargoes into the vacuolar lumen, sorting endosomes mature into multivesicular bodies (MVBs ) through the action of ENDOSOMAL COMPLEX REQUIRED FOR TRANSPORT (ESCRT) protein complexes. MVB -mediated sorting of high-affinity phosphate transporters (PHT1) to the vacuole limits their plasma membrane levels under phosphate-sufficient conditions, a process that allows plants to maintain phosphate homeostasis. Here, we describe ALIX, a cytosolic protein that associates with MVB by interacting with ESCRT-III subunit SNF7 and mediates PHT1;1 trafficking to the vacuole in Arabidopsis thaliana . We show that the partial loss-of-function mutant alix-1 displays reduced vacuolar degradation of PHT1;1. ALIX derivatives containing the alix-1 mutation showed reduced interaction with SNF7, providing a simple molecular explanation for impaired cargo trafficking in alix-1 mutants. In fact, the alix-1 mutation also hampered vacuolar sorting of the brassinosteroid receptor BRI1. We also show that alix-1 displays altered vacuole morphogenesis, implying a new role for ALIX proteins in vacuolar biogenesis, likely acting as part of ESCRT-III complexes. In line with a presumed broad target spectrum, the alix-1 mutation is pleiotropic, leading to reduced plant growth and late flowering, with stronger alix mutations being lethal, indicating that ALIX participates in diverse processes in plants essential for their life.